Exploring Primary Care Streaming Pathway in Emergency Departments in Saudi Arabia: A Qualitative Study - Marwah Hawsawi; Bayan Alilyyani (Emergency Medicine International)
Background. Due to significant emergency department overcrowding, some hospitals implemented a system of directing certain patients who were deemed not in need of emergency care to other facilities called triage away. Pathways were developed as ways to stream patient from emergency departments to primary healthcare who is presenting with less urgent or nonurgent conditions. Thus, the purpose of this study was to explore the pathways (process) for streaming patients from emergency department to primary healthcare at three different sites across Western Region of Saudi Arabia and to identify the streaming criteria and guidance. Materials and Methods. This study used a qualitative observational design. Data were collected through an unstructured observational approach, with an in-depth case study observation involving three emergency departments in the Western Region. Data were collected over three months until data saturated and recorded in the form of filed notes. Results. The results of this study explored that all CTAS-5 were streamed away either (off-site) or (on-site) from emergency department. The average of the sorting/triage cases were around 200 to 250 per shift, and about third to half of them were streamed to Primary Health Centre or Urgent Care Clinic. The total streamed patients were ranging from 50 to 60 per shift, which mean 15–20 case per hour. The study highlighted many factors that influence the practice and decision of streaming. Conclusions. In general, the term “streaming” was not as widely known among emergency clinicians, as was the term “triage.” However, streaming was performed as an evidence-based practice, and clinicians routinely acted to direct patients based on hospital policies. Although, in one hospital, some nurses hack the system to manage the flow of patients based on their intuition. In contrast, the nurses in another hospital emphasised the importance of experience and confidence in streaming improvement.